Evaluation of Students' Cognitive and Affective Development in the Implementation of the Independent Curriculum at Madrasah Ibtidaiyah - Kholis Kholis (LP2M IAI Al-Khairat Pamekasan, 2026)
The implementation of Kurikulum Merdeka in Madrasah Ibtidaiyah represents a strategic effort to promote holistic student development, encompassing both cognitive and affective domains. This study aims to evaluate the cognitive and affective development of students within the implementation of the curriculum. The research employs a qualitative approach with a descriptive-evaluative design. Data were collected through observations, in-depth interviews, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the implementation of Kurikulum Merdeka contributes positively to students’ cognitive development, particularly in enhancing critical thinking, conceptual understanding, and problem-solving skills through contextual and project-based learning. In addition, students’ affective development, including discipline, responsibility, cooperation, and value internalization, also shows significant improvement. However, the evaluation of the affective domain has not been optimally implemented. Assessment practices remain predominantly focused on cognitive aspects, while affective evaluation tends to be subjective and lacks standardized instruments.The study concludes that although Kurikulum Merdeka has successfully fostered holistic learning, there is a need to strengthen evaluation systems, particularly in the affective domain. Therefore, improving teachers’ competencies in authentic assessment, developing comprehensive evaluation instruments, and enhancing institutional support are essential to ensure balanced and effective student development.